A new monotypic genus of Dactylomyiini (Diptera: Dolichopodidae: Neurigoninae) from the Brazilian Chaco, with a discussion on the evolution of the lateral epandrial lobe - Quevedo, Lucas; Capellari, Renato S.; Lamas, Carlos José E. (Zootaxa, 2024)
A new monotypic genus of Neurigoninae (Diptera: Dolichopodidae), Naglisia gracilis gen. et sp. nov., is described from the Chaco of Mato Grosso do Sul, Brazil. It belongs to the tribe Dactylomyiini and is argued to be closely related to Dactylomyia Aldrich plus Macrodactylomyia Naglis, sharing with them the absence of one claw on the male foreleg, the lateral epandrial lobe fused with ventral surstylus, and the distinct morphology of the postgonites. In addition, an updated identification key to the genera of Dactylomyiini and a short discussion on the homology and evolution of the epandrial lobe and surstylus in the tribe are provided.